Revenge prey - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Prey novel., 2026)
"Lucas Davenport must track down a ruthless Russian hit team, in this latest thriller from #1 New York Times bestselling author John Sandford. Leonard Summers--not his real name-- is on the run. A former high-ranking Russian intelligence officer who defected to the U.S. after providing critical information about Russian spies in U.S. government service. Leonard has spent the past year holed up in a CIA facility near Washington with his wife and son. After the CIA makes a deal with the U.S. Marshal Service's Witness Protection Program (WPP), Leonard's family is transported to Minneapolis. The plan is to hide them in a wooded Minneapolis suburb that resembles their former home and dacha near Moscow. The Summerses are received at their destination by Lucas Davenport and fellow marshal Shelly White. Unbeknownst to them, the WPP group has been tracked by a Russian hit team. And while nobody in the WPP has ever been attacked... Leonard might be the first victim. As shots are fired and enemies dodged, Lucas must move quickly to uncover where the leak is coming from, before the hit team can strike again."-- Provided by publisher.